KEEFEKTIFAN MEDIA PICTURE WORD DALAM MENINGKATKAN PENGUASAAN KOSAKATA BAHASA JEPANG SISWA KELAS X SMA TARUNA MANDIRI PEKANBARU - Ayu Angriani; Hadriana Hadriana; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : Media has an important role in language learning. therefore the use of media is needed in learning activities in order to be more creative, innovative and active. This study discusses the use of Picture Word media in learning Japanese vocabulary in tenth grade students of TarunaMandiri High School Pekanbaru.The purpose of this study was to find out whether the use of Picture Word media was effective in increasing mastery of Japanese vocabulary in tenth grade students of Taruna Mandiri High School Pekanbaru.This study used an experimental design (pretest-posttest Control group design) conducted on two randomly selected groups namely the experiment group and the control group.The subjects of this study were the tenth grade students of the Taruna Mandiri High School Pekanbaru 2018/2019 school year which consisted of two classes, tenth grade of social as Experiment class and tenth grade of Science 2as control class.The technique of collecting data is done by carrying out the pre-test and post-test, then the results of the test are processed using SPSS Version 23 IBM For Windows.Based on data analysis, the use of Picture Word media can improve student learning outcomes in Japanese vocabulary learning compared to students vocabulary learning outcomes with conventional methods. This can be seen based on the value of the results of the experimental class pretest and posttest having increased 89.9 for the average value in the experimental class and 82.9 in the control class.Key Words: Picture Word media, Japanese vocabulary, Effectiveness.